2019
DOI: 10.1098/rsif.2019.0448
|View full text |Cite
|
Sign up to set email alerts
|

Fungal artillery of zombie flies: infectious spore dispersal using a soft water cannon

Abstract: Dead sporulating female fly cadavers infected by the house fly-pathogenic fungus Entomophthora muscae are attractive to healthy male flies, which by their physical inspection may mechanically trigger spore release and by their movement create whirlwind airflows that covers them in infectious conidia. The fungal artillery of E. muscae protrudes outward from the fly cadaver, and consists of a plethora of micrometric stalks that each uses a liquid-based turgor press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Though there was once disagreement regarding the ejection mechanism of E. muscae primary conidia from conidiophores, recent work has conclusively demonstrated that primary conidia are fired using a water cannon mechanism (de Ruiter et al 2019 ). Each primary conidium is surrounded by a characteristic “halo” of material when landed on a surface.…”
Section: Infection and The Fungal Life-cycle Within The Hostmentioning
confidence: 99%
“…Though there was once disagreement regarding the ejection mechanism of E. muscae primary conidia from conidiophores, recent work has conclusively demonstrated that primary conidia are fired using a water cannon mechanism (de Ruiter et al 2019 ). Each primary conidium is surrounded by a characteristic “halo” of material when landed on a surface.…”
Section: Infection and The Fungal Life-cycle Within The Hostmentioning
confidence: 99%
“…Elastic recoil is often studied in animals where muscles load energy into springs, but diverse ectothermic organisms, from cnidarians to plants and fungi, use rapid release of energy that was stored slowly in tissues or fluid to fire nematocysts, seeds and spores, respectively, or to capture prey (Berg et al, 2019;de Ruiter et al, 2019;Edwards et al, 2005;Hayashi et al, 2010;Holstein and Tardent, 1984;Poppinga et al, 2016;Vincent et al, 2011). In cases where muscle cannot be described as a default motor for comparison, temperature effects on alternative physiological motors can be used to assess thermal robustness.…”
Section: Elastic Recoilmentioning
confidence: 99%
“…The entomopathogenic fungus, Entomophthora muscae, represents a unique example in that it not only behaviourally manipulates its immediate house fly (Musca domestica) host, but also appears to manipulate uninfected conspecifics. Prior to death, infected house flies are manipulated to seek out elevated positions and die with wings spread out in a specific posture conducive for active discharge of infectious fungal conidia, which occurs primarily within the first 24 hours post mortem (De Ruiter et al, 2019;Lovett et al, 2020). Male and female flies in the vicinity may become infected from being directly hit by a conidium (spore) or via contact with already-discharged conidia that form a halo on the surface surrounding a conidia-shooting cadaver (De Ruiter et al, 2019).…”
Section: Mainmentioning
confidence: 99%